2015
DOI: 10.1016/j.vaccine.2014.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and reactogenicity of Infanrix™ when co-administered with meningococcal MenACWY-TT conjugate vaccine in toddlers primed with MenHibrix™ and Pediarix™

Abstract: Routine booster DTaP was immunogenic with an acceptable safety profile when co-administered with MenACWY-TT vaccine in HibMenCY-TT-primed toddlers. These data support the administration of a fourth DTaP dose following a 4-dose HibMenCY-TT vaccination series, or co-administered with MenACWY-TT in HibMenCY-TT-primed children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…Systems biology approaches are increasingly being used to describe and define signatures of immunity, initially in the setting of infection but more recently in vaccine-induced responses, leading to the development of systems vaccinology (Querec et al, 2009; Olafsdottir et al, 2015). These transcriptomic analyses have primarily focused on the prediction of vaccine efficacy and immune outcome with the assessment of vaccine safety and potential reactogenicity relying on clinical reactive scores of adverse events (Bucasas et al, 2011; Furman et al, 2013; Obermoser et al, 2013; Vahey et al, 2010; Li et al, 2014; Leonardi et al, 2015; Vesikari et al, 2009). However, the transcriptome can also reveal the intricate details of the very early events after vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Systems biology approaches are increasingly being used to describe and define signatures of immunity, initially in the setting of infection but more recently in vaccine-induced responses, leading to the development of systems vaccinology (Querec et al, 2009; Olafsdottir et al, 2015). These transcriptomic analyses have primarily focused on the prediction of vaccine efficacy and immune outcome with the assessment of vaccine safety and potential reactogenicity relying on clinical reactive scores of adverse events (Bucasas et al, 2011; Furman et al, 2013; Obermoser et al, 2013; Vahey et al, 2010; Li et al, 2014; Leonardi et al, 2015; Vesikari et al, 2009). However, the transcriptome can also reveal the intricate details of the very early events after vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…145 This important finding supported the previously observed cross-protection induced by the monovalent CPS vaccines, 146 and that suggested in the context of a recent clinical trial involving a Hib/MenC/MenY conjugate vaccine, whereby the vaccinees showed significantly higher 30 MenW-specific seroprotection than the control group. 147 Moreover, by demonstrating the partial overlap between the two CPS dynamics, the molecular simulation study also provided some insights on the superior capacity of the MenY CPS to induce crossprotection with MenW. 145 The similarity between the MenY and MenW CPS extends to their O-acetylation 35 pattern.…”
mentioning
confidence: 98%
“…Study MET50 documented lower GMCs against some of the pertussis antigens upon concomitant administration of MenACYW-TT with Tdap [63]. However, the clinical relevance of this observation is unclear considering that there is no established immune correlate of protection for pertussis and lower anti-pertussis antibody concentrations have also been documented upon concomitant administration of MCV4-CRM and MCV4-TT with vaccines incorporating pertussis antigens [89][90][91].…”
Section: Expert Opinionmentioning
confidence: 99%